2024
DOI: 10.1002/adfm.202311730
|View full text |Cite
|
Sign up to set email alerts
|

Auger‐Assisted Secondary Hot Carrier Transfer in a Type I MoS2/PtSe2 Heterostructure

Jin Yang,
Shaokuan Gong,
Xiaguang Zhang
et al.

Abstract: Charge transfer is vital in determining the optoelectronic properties of atomically thin materials, yet remains elusive in type I heterostructures. Here, distinct two‐step charge transfer processes in a type I MoS2/PtSe2 heterostructure are reported. By exclusively exciting the smaller bandgap PtSe2, strong exciton photobleaching peaks of the larger bandgap MoS2 are observed, indicating primary hot carrier transfer from PtSe2 to MoS2 within 70 fs. More importantly, the amplitude of the exciton peaks shows a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The value of Δ v (the distance between the E 1 2g and A 1g mode Raman shifts of MoS 2 ) decreases when the E 1 2g blue-shifted for the MoS 2 of the GMS nanoheterostructures, it is shown that the tensile strain of MoS 2 decreases because of the perfect lattice matching between MoS 2 and Ga 2 O 3 when the GMS nanoheterostructures are formed. Under different sputtering powers, the A 1g peak of MoS 2 is slightly red-shifted, which can be attributed to the following reasons: (1) The A 1g vibrational mode is reported to be more sensitive to electron transfer in MoS 2. The formation of GMS nanoheterostructures leads to the recombination of excitons and the emergence of new defect state energy levels. The slight red-shift of A 1g can be attributed to the transfer of electrons from Ga 2 O 3 to MoS 2 , resulting in an increased electron density of MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of Δ v (the distance between the E 1 2g and A 1g mode Raman shifts of MoS 2 ) decreases when the E 1 2g blue-shifted for the MoS 2 of the GMS nanoheterostructures, it is shown that the tensile strain of MoS 2 decreases because of the perfect lattice matching between MoS 2 and Ga 2 O 3 when the GMS nanoheterostructures are formed. Under different sputtering powers, the A 1g peak of MoS 2 is slightly red-shifted, which can be attributed to the following reasons: (1) The A 1g vibrational mode is reported to be more sensitive to electron transfer in MoS 2. The formation of GMS nanoheterostructures leads to the recombination of excitons and the emergence of new defect state energy levels. The slight red-shift of A 1g can be attributed to the transfer of electrons from Ga 2 O 3 to MoS 2 , resulting in an increased electron density of MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of a type I heterostructure allows electrons and holes to be confined to the same material, thus significantly enhancing the light–matter interaction . The application of type I heterostructures in the field of photocatalysis is realized through the process of hot carrier transfer …”
Section: Introductionmentioning
confidence: 99%